2014
DOI: 10.1542/peds.2013-4011
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Variation in the Use of Inhaled Nitric Oxide

Abstract: BACKGROUND AND OBJECTIVE: Decreasing practice variation and following clinical guidelines improve patient outcomes and reduce costs. Inhaled nitric oxide (iNO) is an effective but expensive treatment of pulmonary hypertension and right heart failure in patients with congenital or acquired heart disease. Our objective was to implement standardized initiation and weaning guidelines for iNO usage in the cardiothoracic ICU (CTICU) to reduce variation in use while maintaining quality patient care.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
0
14
0
1
Order By: Relevance
“…Clinical practice guidelines are widely regarded as key to reducing practice variation and improving the quality of care. 29,33 However, to be effective, guidelines must be updated regularly to reflect current evidence or expert opinion, must be minimally controversial to ensure maximum buy-in, and must be implemented in an environment characterized by sustained communication and vigilance. The stewardship model has been used successfully in the pediatric setting to promote safe and evidence-based use of antimicrobial agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical practice guidelines are widely regarded as key to reducing practice variation and improving the quality of care. 29,33 However, to be effective, guidelines must be updated regularly to reflect current evidence or expert opinion, must be minimally controversial to ensure maximum buy-in, and must be implemented in an environment characterized by sustained communication and vigilance. The stewardship model has been used successfully in the pediatric setting to promote safe and evidence-based use of antimicrobial agents.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28] At best, such practices have major economic consequences; at worst, have the potential to cause harm. Lack of adherence to guidelines relating to commencement and weaning of iNO therapy represents another practice with major economic and patient safety implications 29 ; however, compliance with guidelines relating to iNO use has not been previously examined in the NICU setting.…”
mentioning
confidence: 99%
“… Nationwide Children’s Hospital PICU iNO treatment guidelines, including criteria for starting, response, and weaning. *Cardiac patients identified with pulmonary hypertension were managed according to a separate protocol described by Simsic et al 14 P/F ratio is the arterial partial pressure of oxygen to the fraction of inspired oxygen. When arterial blood gases were not available, the S/F ratio or oxygen saturation to fraction of inspired oxygen was used.…”
Section: Methodsmentioning
confidence: 99%
“…12,13 INO is often SEE THE ORIGINAL STUDY ON PAGE 644 prescribed to treat pulmonary hypertension in the cardiac ICU setting; however, its overall effectiveness in improving outcomes and in comparison with other available pulmonary vasodilators has yet to be determined. In addition, Simsic et al 14 reported that the use of an INO protocol in this subject population reduced variation, but not utilization or cost. This is in contrast to a study in this issue of RESPIRATORY CARE.…”
mentioning
confidence: 86%